Effects of the superheater layout on the thermal performance of a central cavity receiver. (25th July 2019) - Tu, Nan; Fang, Jiabin; Wan, Zhenjie; Wei, Jinjia
Highlights: A thermal simulation approach previously raised for cavity receiver was adopted. The thermal elasticity theory was used to quantify the receiver thermal stress. The heat flux of the receiver under different superheater locations were studied. The thermal efficiency and the outlet temperature of the receiver were analyzed. The relationship between the steam temperature and the incident power was found. Abstract: For a water/steam solar cavity receiver, the superheater usually works at a very high temperature. It is necessary to consider the installation location of the superheater inside the cavity for its safe operation. In the present work, the effects of the superheater layouts on the thermal performance of the receiver were numerically investigated. A computational model was proposed to solve both the heat transfer and the thermal stress. With this model, the heat losses of the receiver and the temperature distributions were obtained under different superheater locations. Besides, the thermal elasticity theory was employed to quantify the thermal stress in the superheater. The results showed that the heat flux of the superheater apparently drops when it is moved from the center to the upper zone of the cavity. Consequently, the maximum wall temperature of the superheater is remarkably reduced from 740℃ to 470℃, resulting in the reduction of thermal stress by 50% approximately. In addition, due to the cavity effect, the thermal efficiency of the receiver changes slightly as the superheater location varies. Moreover, with the incident power rising, the boiler and superheater panels can absorb more solar radiation simultaneously, since they are installed together inside the cavity. It will lead to the evaporation rate and flowrate of superheated steam increasing. Therefore, the outlet temperature of superheated steam has no obvious change even though the incident power varies significantly.